Patterns and costs of health‐care utilisation in Australian children: The first 5 years. (9th November 2018) - Hayes, Alison J; Brown, Victoria; Tan, Eng Joo; Chevalier, Anna; D'Souza, Mario; Rissel, Chris; Baur, Louise A; Wen, Li Ming; Moodie, Marj L
Abstract : Aim: To describe patterns of health‐care utilisation and costs of a cohort of Australian children in the first 5 years of life and to investigate demographic factors associated with high health‐care utilisation. Methods: This was a secondary data analysis of prospectively linked health‐care utilisation data, including primary and secondary health‐care consults, hospitalisations and emergency. The subjects were 350 children from a disadvantaged area of Sydney. Outcomes were the frequency and cost of all health‐care consults from birth to 5 years of age. Multivariable logistic regression examined the odds of being a high health‐care user in relation to child and family characteristics. Results: Children had more health‐care consults and higher annual health‐care costs in the first 2 years of life (mean 12 health‐care visits per year, mean cost Australian dollars (AUD) 1400 per child) than in the next 3 years (8 visits per year, AUD 900 per child). Primary care consults formed 86% of all health‐care encounters but only contributed to 30% of the total costs. Factors positively associated with frequent use of health care in the first 2 years of life included being male, mother not married/ de facto and annual household income of less than AUD 40000. Frequent users mostly accessed primary care services. There was no association between demographic factors and frequent use of health care in years 3–5 of life. Conclusions: Children from low‐income or single‐parent families may require additional support services during the first 2 years of life. Maintaining or increasing access to free or very low‐cost primary health‐care services for disadvantaged families will promote equity in health.